2020
DOI: 10.1155/2020/3808909
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Climate Temperature and Water Stress on Plant Growth and Accumulation of Antioxidant Compounds in Sweet Basil (Ocimum basilicum L.) Leafy Vegetable

Abstract: The effects of climate temperature and water stress on growth and several stress markers were investigated in sweet basil plants. Some growth parameters (shoot length and number of leaves) and photosynthetic chlorophyll contents were determined every two days during plant growth, and foliage leaf material was collected after 15 and 21 days of treatment. Both climate temperature and water stress inhibited sweet basil plant growth; especially, total chlorophyll levels were decreased significantly in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 45 publications
(63 reference statements)
3
52
2
Order By: Relevance
“…While under high-temperature treatment, the index of flavonoids of basil decreased considerably. These findings contradict many studies [31,38,39] because increased flavonoids are usually associated with thermophilic plant defense mechanisms against heat stress. Moreover, increased growth temperature from 30/22 • C to 38/30 • C for basil under elevated CO 2 produced more Anth content.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…While under high-temperature treatment, the index of flavonoids of basil decreased considerably. These findings contradict many studies [31,38,39] because increased flavonoids are usually associated with thermophilic plant defense mechanisms against heat stress. Moreover, increased growth temperature from 30/22 • C to 38/30 • C for basil under elevated CO 2 produced more Anth content.…”
Section: Discussioncontrasting
confidence: 85%
“…In this current research, increasing the temperature to 38/30 • C at ambient CO 2 concentration caused less adverse effects on the early season's morphological features (17 DAT) of basil. Previous research indicated an increase in the PH, NN, and BN primarily because basil plants prefer warmer temperatures [31]. For instance, in this current study, high-temperature stress caused a significant decrease in late-season basil PH, NN, and BN by 17%, 16%, 18%, respectively, compared to the control treatments.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, basil leaves subjected to low-temperature stress were identified to experience chlorosis due to rapid degradation of carotenoid, chlorophyll, and antioxidant content [11,18]. It is important to note that the alteration of basil leaf pigments due to chilling stress could damage the photosynthetic apparatus, with detrimental impacts on plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an increased chlorophyll a / b ratio and decrease in chlorophyll to carotenoid ratio can be seen in heat-tolerant cultivar [ 5 , 22 ]. Al-Huqail et al [ 14 ] showed total chlorophyll reduction in basil leaves under high temperature; however, the authors did not indicate a specific genotype used in this study. In our study, both short-term chilling and heat stress caused a significant increase in chlorophyll a , chlorophyll b , and carotenoid content in leaves of tested basil cultivar.…”
Section: Discussionmentioning
confidence: 74%
“…It is known that, because of a poor tolerance of young leaves and buds to low temperature in cultivated plants, a sudden frost in early spring causes cold stress and negatively affect the commercial yield, whereas the combination of warmer maximum temperatures leads to earlier budburst and greater risk of damage [ 8 ]. Therefore, in order to develop improved crops with complete yield potential, it is important to understand the numerous plant mechanisms and their interactions during abiotic stresses and to explore the ways to improve the temperature tolerance of basil plants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%